Assistance for Disaster Preparedness Volunteer Students: Lifting Moving and the Process of Evacuating Disaster Victims - Indri Wahyuningsih; Risa Herlianita; Maya Iriyani (Jurnal Pengabdian Masyarakat Bestari, 2023)
Disaster management includes pre-disaster, emergency response and post-disaster stages. The partners of this activity are student volunteers for disaster preparedness (Maharesigana), a community formed as a forum for fostering and developing students in disaster risk reduction, community service in handling disaster preparedness, and carrying out disaster management activities. However, a scientific background (non-health) becomes an obstacle when on duty. This activity aims to provide assistance in improving skills and knowledge of evacuation techniques and lifting moving procedures which are basic skills that partners must have. The activity method is delivered in the form of lectures, demonstrations, independent practice and role play simulations based on case scenarios. The results of the evaluation in the form of post tests and skills showed positive results in the aspects of knowledge (average score 82) and skills (average score 80).